2012
DOI: 10.1016/j.abb.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D safety and requirements

Abstract: Vitamin D an ancient secosteroid is essential for mineral homeostasis, bone remodeling, immune modulation, and energy metabolism. Recently, debates have emerged about the daily vitamin D requirements for healthy and elderly adults, the safety and efficacy of long term supplementation and the role of vitamin D deficiency in several chronic disease states. Since this molecule acts as both a vitamin and a hormone, it should not be surprising that the effects of supplementation are multi-faceted and complex. Yet d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 121 publications
1
31
0
6
Order By: Relevance
“…The role of vitamin D in nonbone related end points, such as mortality, cardiovascular risk, cancer and autoimmune diseases is still controversial (39,40). There is a consensus that 25(OH)D (calcidiol) is the most abundant metabolite and the best indicator for the evaluation of vitamin D status (A), the indivi duals being classified as: deficient, insufficient of suf ficient in vitamin D (3,6,41,42).…”
Section: What Are the Effects On Bone Metabolism?mentioning
confidence: 99%
“…The role of vitamin D in nonbone related end points, such as mortality, cardiovascular risk, cancer and autoimmune diseases is still controversial (39,40). There is a consensus that 25(OH)D (calcidiol) is the most abundant metabolite and the best indicator for the evaluation of vitamin D status (A), the indivi duals being classified as: deficient, insufficient of suf ficient in vitamin D (3,6,41,42).…”
Section: What Are the Effects On Bone Metabolism?mentioning
confidence: 99%
“…Several studies have shown that low serum levels of 25[OH]D are common in MS patients throughout the world, particularly in those with advanced disability [27,64,95,[121][122][123]. The optimal 25[OH]D level for maintenance of bone health is, however, debated [124,125]. Several researchers argue that it should be ≥75 nmol/l [126].…”
Section: Conclusion and Expert Commentarymentioning
confidence: 98%
“…D vitamini düşüklüğünün, osteomalazi ve osteoporoz (OP) gibi metabolik kemik hastalıklarının yanı sıra kanser, diyabet, multipl skleroz ve kardiyovasküler olaylar ile ilişkisi tespit edilmiştir (1)(2)(3)(4). D vitamininin, kalsiyum metabolizması yanında güçlü immün modulatuvar etkileri de vardır (5). Genel olarak <30 mcg/L hipovitaminoz, 50 mcg/L optimal kabul edilmekle birlikte, optimal 25(OH)D serum düzeyleri konusunda farklı ülkelerden farklı görüşler bildirilmektedir.…”
Section: Introductionunclassified